Bob Dylan and Leonard Cohen deaths and entrances - Boucher, David 1951-; Boucher, Lucy (Bloomsbury Academic, 2021)
"Both Dylan and Cohen have been a presence on the music and poetry landscape spanning six decades. This book begins with a discussion of their contemporary importance, and how they have sustained their enduring appeal as performers and recording artists. The focus then returns to their ambitions when they first started out, arguing that they both shared the aspirations of the Beat Generation of Ginsberg, Kerouac and Corso to be as famous as Dylan Thomas and live the life of his sense of unconditional social irresponsibility. The 'Rimbaud of Cwmdonkin Drive' took America by storm, demonstrating that the bohemian poet could earn a living outside the academy. The fame of Dylan and Cohen, while it fluctuated over the decades, was sustained and was sustainable because they self-consciously adopted different personas, or masks, to distance themselves from the public self. This necessarily requires an exploration of their relation to religion as avenues to find and preserve their inner identities. Their lyrics and poetry are explored in the context of the relation between poetry and song, and of Lorca's concepts of the poetry of inspiration, and the deep dark emotional depths of 'duende.' Such ideas draw upon the dislocation of the mind, and the liberation of the senses that so struck Dylan and Cohen when they first read the poetry and letters of Arthur Rimbaud and Federico García Lorca. We see that the performance and the poetry are integral, and the 'duende,' or passion, of the delivery, is inseparable from the lyric or poetry, and common to Dylan, Cohen and the Beat Generation"--
Keywords: Cohen, Leonard -- 1934-2016; Dylan, Bob -- 1941-; Dylan, Bob / 1941-; Cohen, Leonard / 1934-2016; Singers / United States / Biography; Singers / Canada / Biography; Singers; Canada; United States; Biographies; Biografie